Concomitant use of polarization and negative phase contrast microscopy for the study of microorganisms - Žižka, Zdeněk (Folia microbiologica, 2018)
A simultaneous application of negative phase contrast and polarization microscopy was used to study the internal structure of microbial cells. Negative phase contrast allowed us to display the fine cell structures with a refractive index of light approaching that of the environment, e.g., the cytoplasm, and converted an invisible phase image to a visible amplitude one. In the polarizing microscope, cross-polarizing filters, together with first-order quartz compensator and a turntable, showed maximum birefringence of individual structures. Material containing algae was collected in ponds in the villages Sýkořice and Zbečno (Protected Landscape Area Křivoklátsko). Objects were studied in a laboratory microscope (Carl Zeiss Jena, type NfpK), equipped with a basic body In Ph 160 with an exchangeable module Ph, LOMO St. Petersburg turntable mounted on a centering holder of our own construction and a Nikon D 70 digital SLR camera. Anisotropic granules were found only in the members of two orders of algae (Euglenales, Euglenophyceae and Chlorococcales, Chlorophyceae). They always showed strong birefringence and differed in both number and size. An important finding concerned thin pellicles in genus Euglena (Euglenales, Euglenophyceae) which exhibited weak birefringence. In genus Pediastrum (Chlorococcales, Chlorophyceae), these granules were found only in living coenobium cells. In contrast, dead coenobium cells contained many granules without birefringence-an important finding. Another important finding included birefringent lamellar structure of the transverse cell wall and weak birefringence of pyrenoids in filamentous algae of genus Spirogyra (Zygnematales, Conjugatophyceae). It was clearly displayed by the negative phase contrast and has not been documented by other methods. This method can also record the very weak birefringence of the frustule of a diatom of genus Pinnularia (Naviculales, Bacillariophyceae), which was further reinforced by the use of quartz compensator-an important finding. Simultaneous use of negative phase contrast and polarization microscopy allowed us to study not only birefringent granules of storage substances in microorganisms, but also the individual lamellae of the cell walls of filamentous algae and very thin frustule walls in diatoms. These can be visualized only by this contrast method, which provides a higher resolution (subjective opinion only) than other methods such as positive phase contrast or relief contrast.
Keywords: Cell Biology; biologie buňky; rozsivky; cytologické techniky; Euglenida; Microscopy, Phase-Contrast; dvojitý lom; Anisotropy; Chlorophyta; polarizační mikroskopie; Zygnematales; Cytological Techniques; Microscopy, Polarization; anizotropie; buněčná stěna; Cell Wall; Birefringence; Diatoms; Cytoplasm; cytoplazma; mikroskopie fázově kontrastní